Meenoostahtan Minisiwin: First Nations Family Justice "Pathways to Peace" - Pintarics, Joe; Sveinunggaard, Karen (First Peoples Child & Family Review, 2005)
Community justice initiatives are now common in Canada, both for young offenders and in adult criminal cases; there are only a few examples of alternative methods for dealing with justice issues in the area of mandated child welfare services. The initiative outlined in this paper represents one of the most comprehensive family justice initiatives in First Nations Child and Family Services in Canada. Meenoostahtan Minisiwin: First Nations Family Justice offers a new way of addressing conflict in child and family matters, outside of the regular Child and Family Services (CFS) and court systems. It incorporates the traditional peacemaking role that has existed for centuries in Northern Manitoba Cree communities, alongside contemporary family mediation. The program brings together family, extended family, community members, Elders, social workers and community service providers in the resolution of child protection concerns through the use of properly trained Okweskimowewak (family mediators). The Okweskimowewak’s role involves assisting participants to articulate their personal ‘truth’ (dabwe) and to hear and respect the dabwe of others; to create a safe and nurturing context by addressing inherent power imbalances; to explore the root causes of family conflict in order to address the long term best interests of children; and to facilitate innovative and collaborative planning outcomes for families. The program was developed by the Awasis Agency of Northern Manitoba, a mandated First Nations Child and Family Services agency, although it receives its services mandate from the Manitoba Keewatinowi Okimakanak (MKO) Exectuive. It is jointly funded by the Aboriginal Justice Strategy of Justice Canada and the Manitoba Department of Family Services and Housing. Overall direction for the program is provided by the First Nations Family Justice Committee, a sub-committee of the MKO Exectuive Director of Awasis Agency, and representative chiefs of the MKO region. The program currently employs a Program Coordinator, two full time regional Okweskimowewak, two full time community-based Okweskimowewak and an administrative assistant. Since its inception in 1999, the program has received referrals involving more than seven hundred families, including well over 1900 children and 1500 volunteer participants. Services have been provided in seventeen First Nation communities in Northern Manitoba as well as in Thompson, Winnipeg, The Pas, and Gillam. The Meenoostahtan Minisiwin program responds to all aspects of mandated child welfare, as well as other situations where the best interests of children are in jeopardy. These have included mediating care placement arrangements; child-parent conflicts; family-agency or family-agency-system conflicts; assisting in the development of service plans in neglect and abuse cases; advocating on behalf of families attempting to access services; family violence; larger community-wide conflicts; and working to address systemic problems which impact the lives of First Nations children and families. We believe that by establishing processes which focus on restoring balance and harmony within families and communities, we are working towards an overall increase in the health and wellness of community members.And you who would understand justice, How shall you, unless you Look upon all deeds In the fullness of light? Only then shall you know that the erect And the fallen are but one man standing in The twilight between the Night of his pigmy-self And the day of his god-self. K. Gibran